Democracy, Bureaucracy, and the Study of Administration - Camilla Stivers (Westview Press, 2001)
The essays collected in this volume address several of the most central and enduring ideas in the field of public administration. All appeared originally either in Public Administration Review or another of the journals sponsored by the American Society for Public Administration. This volume focuses on themes that cross subdisciplinary and topical boundaries in the field of public administration. They are as relevant to public budgeting as they are to performance measurement, human resource management, and issues of diversity. They are what Dwight Waldo, a former editor of Public Administration Review, referred to as "political theories," that is, they deal with issues that are ultimately unresolvable yet crucial to a sound understanding of the nature of public administration and to good practice. In a real sense, the existence of this volume constitutes a tribute to Waldo, whose vision of public administration as both a set of practical techniques and a political philosophy contributed so much to the subsequent development of the field.